Design of Student Worksheets based on Learning Cycle to Improve Ability of Mathematics Representation Students of Class VIII Junior High School in Indonesia - Amran, Hasanatul Fu’adah; man, Supar (International Journal of Engineering and Technology, 2018)
Mathematical representation is very important for students because it can affect students regarding material and problem-solving. Application of the 5E learning cycle learning model can help overcome student difficulties in mathematical modeling and geometry understanding. Student worksheets simplify the execution of the learning cycle and can train the ability of mathematical representation. This article aims to develop learning products in the form of a Learning Cycle-based student worksheet that is oriented towards students' mathematical representation abilities. This research is development research with 4D: define, design, development, and dissemination. This research was conducted in class VIII MTs Mu'allimmat Yogyakarta, Indonesia. Subjects in this research were teachers, students, material experts and media experts. Data collection methods used in this research are interviews, questionnaires, and tests. Instruments used in the form of validation sheet, teacher response questionnaire, student response questionnaire, mathematical representation and interview guidance test. The first stage in this research is the analysis of student needs on the student worksheet. The results of the analysis aim to simplify the process of designing student worksheets. The learning cycle stages of Engage make student worksheet design, Explore, Explain, Elaborate, and Evaluate. Pretest and posttest will measure the improvement of students' mathematical representation before and after the use of student worksheets. This research is limited to the design phase. For further research will proceed at the stage of development and dissemination.